MiR-155 inhibits the sensitivity of lung cancer cells to cisplatin via negative regulation of Apaf-1 expression - Zang, Y-S; Zhong, Y-F; Fang, Z; Li, B; An, J (Cancer gene therapy, 2012)
MicroRNA-155 (miR-155) overexpression is often found in malignancies including lung cancer. The objective of this study is to verify the hypothesis, based on the results of bioinformatics analysis, that miR-155 modulates cellular apoptosis and DNA damage through the regulation of Apaf-1 and is thus involved in the development and progression of lung cancer. First, we measured the expression of miR-155 and the Apaf-1 protein in lung cancer tissues. The results showed that expression of miR-155 was significantly higher in lung cancer tissues than in paracancerous and normal tissues; whereas Apaf-1 expression was lower in the lung cancerous tissues. We then established miR-155-silenced and Apaf-1-overexpressed A549 cell lines by transfection with pMAGic2.0-BIC-siRNA and pcDNA3.1-Apaf-1, respectively. These cell lines were then treated with cisplatin, and apoptosis and DNA damage were assessed, with non-transfected A549 cells used as negative controls. The results showed that, relative to controls, the silencing of miR-155 resulted in elevated expression of the Apaf-1 protein, whereas Apaf-1 mRNA levels remained unchanged. Both the silencing of miR-155 and the overexpression Apaf-1 greatly increased the sensitivity of A549 cells to cisplatin treatment, as evidenced by elevated rates of apoptosis and DNA damage. Furthermore, dual-transfection of A549 cells with miR-155 siRNA and Apaf-1 siRNA resulted in the attenuation of apoptosis and DNA damage. In conclusion, the inhibition of miR-155 can enhance the sensitivity of A549 cells to cisplatin treatment by modulation of cellular apoptosis and DNA damage through an Apaf-1-mediated pathway.